Utilisation of Carnival: Case of north-eastern Slovenia - Peter Simonič (University of Belgrade, 2016)
Article/presentation focuses on two Carnivals, which can reveal socio-economic and cultural conditions and continuum of traditional culture. The first one is the most important Carnival in Slovenia named Kurentovanje in Ptuj. The second one takes place in Maribor, the capitol of the region of Štajerska. Article analyses these carnivals as an excellent cases of invented tradition transformed in the process of commercialisation and nationalisation.